2011
DOI: 10.1038/modpathol.2010.229
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 and CDK4 immunohistochemistry is a valuable tool in the differential diagnosis of low-grade osteosarcomas and other primary fibro-osseous lesions of the bone

Abstract: Low-grade osteosarcoma is a rare malignancy that may be subdivided into two main subgroups on the basis of location in relation to the bone cortex, that is, parosteal osteosarcoma and low-grade central osteosarcoma. Their histological appearance is quite similar and characterized by spindle cell stroma with low-to-moderate cellularity and well-differentiated anastomosing bone trabeculae. Low-grade osteosarcomas have a simple genetic profile with supernumerary ring chromosomes comprising amplification of chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
122
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(129 citation statements)
references
References 59 publications
6
122
1
Order By: Relevance
“…24 Although rare in jawbone locations, 25-27 diagnosis of low-grade osteosarcoma should be considered in the context of fibro-osseous lesions due to its specific management. 28,29 Overexpression and gene amplification of MDM2 in low-grade/dedifferentiated osteosarcomas, linked to supernumerary ring 12q13-15 chromosomes containing MDM2, 22,30 have together been proven to be a sensitive and specific diagnostic tool for these tumors in extragnathic locations. Unlike fibrous dysplasia and low-grade osteosarcoma, no recurrent genetic abnormalities have been reported for ossifying fibroma, which remains a lesion of uncertain nature, arising from the periodontal ligament.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 Although rare in jawbone locations, 25-27 diagnosis of low-grade osteosarcoma should be considered in the context of fibro-osseous lesions due to its specific management. 28,29 Overexpression and gene amplification of MDM2 in low-grade/dedifferentiated osteosarcomas, linked to supernumerary ring 12q13-15 chromosomes containing MDM2, 22,30 have together been proven to be a sensitive and specific diagnostic tool for these tumors in extragnathic locations. Unlike fibrous dysplasia and low-grade osteosarcoma, no recurrent genetic abnormalities have been reported for ossifying fibroma, which remains a lesion of uncertain nature, arising from the periodontal ligament.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Cytogenetic abnormalities such as supernumerary ring chromosomes, including amplification of chromosome 12q13-15 leading to multiple copies of MDM2, characterize low-grade osteosarcoma. [19][20][21] To differentiate low-grade osteosarcoma from other fibro-osseous lesions, several studies have shown the diagnostic value of detecting overexpression of MDM2 by immunohistochemistry, 22,23 and MDM2 amplification by quantitative real-time PCR (qPCR), comparative genomic hybridization (CGH) array, or fluorescence in situ hybridization (FISH). 22 These studies mostly included cases of fibrous dysplasia and only a few cases of ossifying fibroma (six cases in Dujardin et al and none in Yoshida et al).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Features which should raise the suspicion of an endosteal osteosarcoma include large areas of perforation of the cortical plates, infiltration of the surrounding soft tissue, failure to demonstrate maturation of the mineralized tissue into lobular bone masses and brisk mitotic activity [19]. MDM2 and CDK4 are sensitive markers for the diagnosis of low grade osteosarcomas [20] and may be helpful in differentiating the lace-like neoplastic osteoid from the cellular delicate osteoid and bone trabecula seen in expansive OD's. Trabecular juvenile ossifying fibromas are true neoplasms with an uncontrolled growth potential, affect younger patients and fail to demonstrate lobular maturation of mineralized tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma generally lack reactivity with other markers in the differential diagnostic considerations of a small round blue cell tumor, but MDM2, CDK4, and osteonectin may help in difficult cases. 95,96 Outcome and management. Osteosarcomas of the sinonasal tract must be resected with clear margins if a good outcome is to be expected, but difficult to achieve in this site, with chemotherapy frequently employed.…”
Section: Nut Carcinoma (Squamous Cell Carcinoma)mentioning
confidence: 99%